Peripheral nerve sheath tumour of the equine maxillary sinus. (22nd June 2015) - Federici, M.; Del Chicca, F.; Rütten, M.; Fürst, A.; Bischofberger, A. S.
Summary This case report describes an 8‐year‐old Belgian Warmblood mare that was initially diagnosed and treated for a dental sinusitis. Despite removal of the diseased teeth and appropriate treatment, the sinusitis did not resolve. Over time, growth of a peripheral nerve sheath tumour of the left maxillary sinus became apparent, with recurrence after surgical removal. The clinical, radiographic, computed tomography, magnetic resonance imaging and pathological (gross and histological) findings of the first reported peripheral nerve sheath tumour of the equine paranasal region are described and illustrated.